PENGARUH ETOS KERJA DAN INSENTIF TERHADAP KINERJA KARYAWAN DENGAN PRODUKTIVITAS KERJA SEBAGAI VARIABEL INTERVENING PADA PT MUSDALIFA KARYA MANDIRI - Mohammad Jihat; Nadri Verena Reniban (Jurnal Ekonomi dan Bisnis, 2024)
This research aims to determine the influence of work ethic and incentives on employee performance by using work productivity as an intervening variable at PT. Musdalifa Karya Mandiri. The data collection techniques used in this research are questionnaires, interviews and observations. The research method used in this research is path analysis using the Smart PLS application version 3.2.9 as a data analysis instrument. The research results show that work ethic and incentives have a positive effect on work productivity, work ethic and incentives have a negative effect on employee performance, work productivity has a positive effect on employee performance, and work ethic has a positive effect on employee performance through work productivity as an intervening variable while incentives have a negative effect on employee performance through work productivity as an intervening variable.